THE SUITABILITY OF SUSTAINABLE URBAN POLICY AND THE REALITY OF ALGERIAN CITIES: BETWEEN LOFTY ASPIRATIONS AND POLICY FAILURE - Naimi Khaled; Yahia Amina (International Journal of Innovative Technologies in Social Science, 2024)
Sustainable development policy has faced, and continues to face, ideological and technical challenges when attempting to apply it to the developmental and local realities of Algerian cities, particularly. Despite efforts to bend Algeria's urban policies to conform to global ideologies, it is evident that Algerian cities have failed to achieve this alignment. Attempting to identify the reasons behind the failure to adopt sustainable urban development policies in Algeria is one of the most significant challenges in managing modern Algerian cities. This issue has triggered much speculation and debate. However, it is clear that addressing this topic has often taken an evasive approach, accompanied by violent closure of the file. This reluctance stems from the need to confront the significant gaps in the urban policies of Algerian cities. This research aims to provide an opportunity to examine the inability of urban policies to accept or adapt to effective ideologies and mechanisms like sustainable urban development, which has proven its success in creating cities and urban regions. Additionally, the study explores various challenges shaping urban policy in terms of standards, domains, and organizational forms. This highlights the weight and diversity of sustainable urban planning content, followed immediately by a brief review of Algeria’s National Spatial Planning Policy and its National Sustainable Development Strategy, This occurs amidst the evident major deficiencies in Algerian urban policy, which is marked by significant shortcomings at many levels, if not all, from the top of the planning hierarchy to the grassroots of local urbanities.